Abstracts of the Philippine health laws 2006 - Delas Llagas, Lilian A.; University of the Philippines Manila ([Manila] National Institutes of Health, University of the Philippines Manila, 2006)
"The National Institutes of Health of the University of the Philippines Manila believes in the importance of disseminating research information. A handbook on Abstracts of Philippine Health Laws 2006 is intended primarily as a handy guide for health practitioners, students and health administrators. Interested members of the law profession may use it in their cases as a quick summary of the pertinent laws. Because law is dynamic, this handbook is the first printing of a series of Abstracts of Philippine Health Laws."--Preface.
Promotive : programmes/services -- Advocacy for promotive health; safety -- Social financing of health care; health insurance; health service -- Protective : environmental health ? Practice of profession.
Keywords: Medical laws and legislation -- Philippines; Public health laws -- Philippines